A flavoromics approach to investigate the effect of Saskatoon berry powder on the sensory attributes, acceptability, volatile components, and electronic nose responses of a low-fat frozen yogurt - Ryland, Donna; Thoroski, John; Shariati-Ievari, Shiva; McElrea, April; Goertzen, Alexandre; Dowling, Geraldine M.; Aliani, Michel (Frontiers in Nutrition, 2024)
Introduction Saskatoon berries are grown in Canada and some northwestern states in the United States, and are notable for containing abundant antioxidant polyphenols, vitamins, metal elements, and fiber. To increase consumer interest in and accessibility to Saskatoon berries, some producers have begun to develop processes for refining Saskatoon berries into a powder with an extended shelf life that can be incorporated into a variety of value-added food products. To assess the desirability of this approach, this study sought to determine how the sensory attributes, consumer acceptability, and volatile and non-volatile composition of a plain, Greek-style frozen yogurt (PY) changed when fortified with 16% Saskatoon berry powder (SBP). Greek-style frozen yogurt was chosen as the food to be fortified for this study due to its low fat and relatively high calcium and protein content as well as its popularity among consumers. Results Descriptive analysis of the two yogurt formulations by 11 participants determined that SBY was higher in berry aroma, berry flavor, and sweetness, and lower in cream aroma, dairy aroma, and sourness compared to PY. SBY was lower in iciness and degree of smoothness and higher in viscosity and mouth coating compared to PY. Untrained participants (n = 112), found no significant differences in color, flavor, and overall acceptability between SBY and PY. However, SBY was significantly less acceptable than PY for texture and aroma. Iciness was the most influential variable related to texture acceptability. For aroma acceptability, berry flavor (negatively related) and berry aroma (positively related) were the most influential attributes. The exposure of Saskatoon berry powder (SBP), PY, and SBY to e-nose sensors showed consistencies in replicate analysis (n = 25 measurements/sample), and cross validation of the PCA showed that the model could sort samples into the correct class with 98.7% accuracy. Key volatile organic compounds (VOCs) responsible for berry and fruity aroma in SBP were also found to be retained in the SBY. Several key phenolic compounds with therapeutic effects such as baicalein, chlorogenate, gallic acid, p-coumaric acid, and syringic acid were also identified in both SBP and SBY samples, potentially indicating that the SBY may retain some of the health benefits associated with the consumption of raw Saskatoon berries.